Exploring the role of open innovation and artificial intelligence in green innovation: A dynamic capabilities approach - Vitor Melão Cassânego; Herick Fernando Moralles; Daniel Luiz de Mattos Nascimento; Guilherme Luz Tortorella (Journal of Innovation & Knowledge, 2025)
Addressing current environmental challenges is not solely a matter of governmental policies. Organizations are key stakeholders who play a vital role through strategic partnerships and adoption of innovative technologies. Based on the dynamic capabilities framework, this research investigates the influence of open innovation partnerships in incorporating corporate green innovation (CGI), specifically green product and process innovation. It also elucidates the potential role of artificial intelligence (AI) capabilities in developing green innovation. Our study, based on a sample of approximately 1780 firms from 93 countries distributed across five continents, show that firms actively searching for and consolidating partnerships in open innovation can enhance green innovation in products and processes. Similarly, firms that develop or incorporate AI capabilities can catalyze the output of green product and process innovation because they incentivize open innovation partnerships, indicating that adopting both simultaneously is preferable. The results also show that the impact on green process innovation is greater than the impact on green product innovation. We recommend that policymakers and firms invest in AI capabilities and open green partnerships, leveraging these synergies to enhance innovation efficiency, and adapt green strategies to varying technological, institutional, and regional contexts.